Agroforestry systems in Africa: Role in livestock production and protection of the environment - Dzowela, B.H.; Mohamed-Saleem, M.A. (Australian Centre for International Agricultural Research, 1994)
Agroforestry practices and systems for supporting pastoral and agropastoral livestock production in Africa range from the preservation of trees to more intensively planted and managed systems. In the extensive traditional practice of tree conservation, use strategy is geared towards biomass maintenance rather than production. Certain native tree species are protected for their fodder value in grazing and crop lands. A mixture of livestock, grazers and browsers make the best use of vegetation types and forms. In intensively managed agroforestry systems of mixed crop-livestock production, leguminous multipurpose trees are planted as fodder banks, alley-farmed or planted as contour-bund hedges. Plantation crop understoreys are planted to aid nutrient cycling and provide high quality supplemental fodders. These agroforestry systems provide potential for environmental protection in sustaining watershed effects of the remaining tropical woodlands. These systems prevent overgrazing by encouraging intensively managed livestock production in zero-grazing systems; arrest deforestation; create a carbon sink through afforestation; reduce soil and water erosion; and sustain the very basis of agricultural productivity for both the crop and livestock subsectors.